Pandemi Covid-19 dan Keberlanjutan Bisnis Mikro-Kecil di Kota Sejarah Gastronomi: Pendekatan Penghidupan Berkelanjutan - Singgalen, Yerik Afrianto (Institut Pertanian Bogor, 2022)
The Covid-19 pandemic causes challenges and threats to micro and small businesses' unsustainability. This study aims to describe the dynamics of micro and small business actors in maintaining business continuity based on a sustainable livelihood framework. This research is located in Salatiga City, Central Java Province, Indonesia. The research method used is qualitative, with a case study approach to traditional culinary businesses and coffee shops. These findings indicate that the Covid-19 pandemic urges the government to take a Large-Scale Social Restrictions (PSBB) policy to the Enforcement of Community Activity Restrictions (PPKM) policy. Also, the obligation to implement health protocols to Clean, Health, Safety, and Environment (CHSE) certification for food and beverage businesses. The policy has limited the mobility and access capabilities of traditional culinary business entrepreneurs and coffee shops to social capital and financial capital, as observed by several culinary businesses and coffee shops that showed a quiet condition of visitors during the PPKM in force. To maintain business continuity during the pandemic, coffee shop entrepreneurs innovate products and business processes by utilizing digital platforms for online marketing; some culinary businesses and coffee shops use service on-demand applications to market food and beverages so that they can be accessed by buyers and still earn income during the PPKM applies. Thus, it shows that diversification and intensification are needed to support sustainable businesses and livelihoods during the Covid-19 pandemic.